The Formation of Kaliningradian Identity - Jankauskas, Paulius (Sociologija. Mintis ir veiksmas, 1998)
The aim of the article is to analyze the Kalingradian identity in terms of the inhabinant’s view on the history of the region. The analysis is developed in a few steps. First, the author discusses the forms of expression of historical memory and their change as factor in the development of both individual and societal self-consiousness. The analysis is developed, second, by understanding those forms as a medium of processes of cultural, political and economical change.